2020
DOI: 10.1186/s12882-020-02133-9
|View full text |Cite
|
Sign up to set email alerts
|

Birth weight and renal markers in children aged 5–10 years in Cameroon: a cross-sectional study

Abstract: Background A relationship exists between birth weight (BW) and glomerular filtration rate (GFR) in postnatal kidney. Willing to fill a gap of knowledge in sub-Saharan Africa, we assessed the effect of BW on blood pressure (BP), proteinuria and GFR among Cameroonians children. Methods This was a cross-sectional hospital-based study from January to April 2018 at the Yaounde Gynaeco-Obstetric and Paediatric Hospital (YGOPH). We recruited low BW (LBW) [< 2500 g], normal BW (NBW) [2500-3999 g] and high BW (HBW… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(12 citation statements)
references
References 37 publications
(44 reference statements)
1
11
0
Order By: Relevance
“…Ramirez et al [32] did not nd any signi cant association between lower BW and proteinuria, which was only associated with the current body weight. In our study, almost 18% of children were found to have pathologic proteinuria (de ned as PCR > 20 mg/mmol), which is higher than the prevalence reported in the general population in children and similar to the previous studies on LBW [33,34]. Pathologic proteinuria is a sign of CKD, which is a known RF for CVD and was found to be associated with LBW [35].…”
Section: Discussionsupporting
confidence: 87%
“…Ramirez et al [32] did not nd any signi cant association between lower BW and proteinuria, which was only associated with the current body weight. In our study, almost 18% of children were found to have pathologic proteinuria (de ned as PCR > 20 mg/mmol), which is higher than the prevalence reported in the general population in children and similar to the previous studies on LBW [33,34]. Pathologic proteinuria is a sign of CKD, which is a known RF for CVD and was found to be associated with LBW [35].…”
Section: Discussionsupporting
confidence: 87%
“…Maternal adverse outcomes were considered as entering intensive care unit (ICU) and taking cesarean section. Low birth weight is considered to <2500 g, high birth weight: ≥4000 g. [ 17 ] Apgar score at the fifth minutes ranges from 0 to 10 is a measure of the neonatal condition based on heart rate, respiration, muscle tone, reflex stimuli and color; Apgar scores at the fifth minutes was divided into 4 groups: Apgar 0 to 3, Apgar 4 to 6, Apgar 7 to 8, and Apgar 9 to 10. [ 18 ] Preterm birth pointed the birth of a live infant before 37 weeks of gestation.…”
Section: Methodsmentioning
confidence: 99%
“…Low birth weight (LBW), a surrogate of exposure to maternal malnutrition, has been also identified as a risk factor for CKD 91 . In addition, studies have demonstrated the link between LBW and childhood hypertension and CKD, and later in life high blood pressure; further contribute to CKD risk 92,93 …”
Section: Resultsmentioning
confidence: 99%
“…91 In addition, studies have demonstrated the link between LBW and childhood hypertension and CKD, and later in life high blood pressure; further contribute to CKD risk. 92,93 Up to 80% of the population in Africa is estimated to use herbal preparations, and this exposure has been associated with kidney injury in Africa and it is recognized to substantially contribute to the CKD burden in the region. 18,54,94,95 The scoping review in Cameroon and a systematic review of studies in Nigeria reported exposure to traditional herbal agents as possible risk factor for CKD.…”
Section: Ckd and Environmental Stressorsmentioning
confidence: 99%